Analysis of the labor insertion of graduates from FACENA engineering programs within the framework of CyMAT - Sanabria, Norberto Argentino (2020)
Fil: Sanabria, Norberto Argentino. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.